Regrowth and Yield of Asystasia gangetica Subsp. Micrantha Feeded Organic Fertilizer Solid Waste of Virgin Coconut Oil with Different Dosage and Decomposition Time - Tarigan, Efraim Primsa; Duarsa, M. Anuraga Putra; Witariadi, N. M. (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak; Vol 12 No 2 (2023): Pastura Vol. 12 No. 2 Tahun 2023DO - 10.24843/Pastura.2023.v12.i02.p05, 2023)
ABSTRACT   This study aimed to determine the effect and interaction between the decomposition time and the dose of organic fertilizer solid waste virgin coconut oil (VCO) on the regrowth and yield of Asystasia gangetica subsp. Micrantha. The research was conducted at the Greenhouse, Sesetan Research Station, Faculty of Animal Husbandry, Udayana University on Jalan Raya Sesetan Gang Markisa, the study lasted for 2 months, using a completely randomized design (CRD) with two factorial pattern. The first factor was the decomposition time: 4 weeks (W4), 2 weeks (W2), and 0 weeks (W0) and the second factor consists of dosage of organic fertilizer for solid waste VCO, namely: 0 ton ha -1 (D0), 10 ton ha -1 (D10), 20 ton ha -1 (D20), and 30 ton ha -1 (D30). There were 12 treatment combinations and each treatment was repeated four times so that there were 48 experimental units. The variables observed were growth variables, yield variables and plant growth characteristics variables. The results showed that there was an interaction between decomposition time and dosage on all variables except for plant height and number of leaves. The decomposition time of 4 weeks and time of 0 weeks gave a better response than the decomposition time of 2 weeks. The best dosage given for regrowth and yield of A. gangetica was 20 ton ha -1 . It was concluded that there was an interaction between the decomposition time and the dosage and the treatment of decomposition time of 4 weeks and a dosage of 20 ton ha -1 gave the best response to the regrowth and yield of A. gangetica subsp. Micrantha.   Keywords: Asystasia gangetica, decomposition, dosage, yield, VCO solid waste, regrowth